EFFECTS OF CASH MANAGEMENT TECHNIQUES ON THE FINANCIAL PERFORMANCE OF COMMERCIAL BANKS IN - SOMALIA, MOGADISHU; AMIN, AHMED MOHAMED (IJRDO - Journal of Business Management, 2017)
The general objective of this study was to investigate the effects of cash management techniques on the financial performance of commercial banks in Mogadishu Somalia. The study population was selected a number of banks such as Dahabshil bank, premier bank and Salaam Somali bank of 100 representatives of commercial banks in Mogadishu. The sample size was 80 staff and management of the population. The study employed a survey research design in data collection. After data processing, statistical techniques of data analysis like (SPSS) version 20 software were used to determine the relationship between cash management techniques and financial performance in commercial banks. The results generally indicate that except for cash disbursement, other independent variables cash planning, cash budgeting and cash collection period were found to have significant and positive correlations on financial performance of commercial banks. There was a weak positive but insignificant correlation between cash disbursement and financial performance of commercial banks. The study recommends that managers of commercial banks in Mogadishu Somalia should employ knowledgeable and qualified personnel that ensure the right decisions of cash management system.